Designing labor market regulations in developing countries - Gordon Betcherman (IZA World of Labor, 2019)
Governments regulate employment to protect workers and improve labor market efficiency. But, regulations, such as minimum wages and job security rules, can be controversial. Thus, decisions on setting employment regulations should be based on empirical evidence of their likely impacts. Research suggests that most countries set regulations in the appropriate range. But this is not always the case and it can be costly when countries over- or underregulate their labor markets. In developing countries, effective regulation also depends on enforcement and education policies that will increase compliance.
Keywords: 330; labor market regulation; job security; minimum wage